The Potential of the Case Study Method for Organisational Analysis - Dopson, S (Policy Press, 2003)
This article explores the case study method with a view to considering its potential contribution for organisational analysis. The promise of this method is seen to lie in allowing complex interdependencies between groups and complex social processes to be explored within a social context. This potential can only be realised if a number of important standards are met. Such standards include using organisational theory, seeking multiple data, comparing cases where possible and a clearly presented research design.